An Efficient and Unconditionally Energy Stable Scheme for Simulating Solid-State Dewetting of Thin Films with Isotropic Surface Energy (Communications in Computational Physics, 2019)
In this paper, we propose highly efficient, unconditionally energy-stable numerical schemes to approximate the isotropic phase field model of solid-state dewetting problems by using the invariant energy quadratization (IEQ) method. The phasefield model is governed by the isotropic Cahn-Hilliard equation with degenerate mobilities and dynamic contact line boundary conditions. By using the backward differential formula to discretize temporal derivatives, we construct linearly first- andsecond-order IEQ schemes for solving the model. It can be rigorously proved thatthese numerical schemes are unconditionally energy-stable and satisfy the total massconservation during the evolution. By performing numerical simulations, we demonstrate that these IEQ-based schemes (including the first-order IEQ/BDF1, second-orderIEQ/BDF2) are highly efficient, accurate and energy-stable. Furthermore, many interesting dewetting phenomena (such as the hole dynamics, pinch-off), are investigatedby using the proposed IEQ schemes.